New, tumour-specific therapy for colorectal cancer patients. (Research'eu results magazine)
The combination of colectomy and chemotherapy can save up to 50-70 percent of patients with colorectal cancer. Those who do not have that chance, however, often see their cancer come back in the form of metastasis. A new, more precise therapy could prevent these relapses and even remove the need for colectomy altogether.